Assessment of flumioxazin soil behavior and thermal stability in aqueous solutions. (February 2022) - Eason, Kayla; Grey, Timothy; Cabrera, Miguel; Basinger, Nicholas; Hurdle, Nicholas
Abstract: Flumioxazin is a preemergence, N -phenylpththalimide herbicide that can be applied to control a broad spectrum of weeds in a variety of cropping systems. Limited information exists concerning the environmental fate of flumioxazin, therefore the present studies investigated the kinetic behavior of flumioxazin in soil and aqueous solution using field and analytical techniques to establish its degradation properties. Flumioxazin half-life in a Greenville sandy clay loam and Faceville loamy sand was 26.6 d. Flumioxazin was determined to have a groundwater ubiquity score of 1.79, indicating a low leachability potential. There was an inverse correlation between flumioxazin concentration in soil, rainfall, and solar radiation. There was no direct correlation between flumioxazin concentration and soil temperature. Flumioxazin activation energy was 58.4 (±1.2) kJ mol −1 with a Q10 value of 2.2. Even at the lowest amount of solar radiation and soil temperature, the energy from these environmental measures exceeded the activation energy needed for flumioxazin degradation. Flumioxazin stability in solution and field dissipation indicate that, with the input of thermal energy, degradation can be rapid. Graphical abstract: Image 1 Highlights: Flumioxazin half-life in two Georgia soils was determined to be 26.6 d with a GUS score of 1.79. The activation energy of flumioxazin was 58.4 (±1.2) kJ mol −1 with a Q10 value of 2.2. Flumioxazin concentration in soil decreased over time as rainfall and solar radiation increased. Flumioxazin stability in aqueous solution indicated that degradation increased as the input of thermal energy rose.